The Unfolding of Value Sources During Online Business Model Transformation - Nadja Hoßbach; Martin Wiener; Carol S. Saunders (Journal of Business Models, 2016)
Purpose: In the magazine publishing industry, viable online business models are still rare to absent. To prepare for the ‘digital future’ and safeguard their long-term survival, many publishers are currently in the process of transforming their online business model. Against this backdrop, this study aims to develop a deeper understanding of (1) how the different building blocks of an online business model are transformed over time and (2) how sources of value creation unfold during this transformation process.